A Double Electrochemical Platform for Ultrasensitive and Simultaneous Determination of 6-Mercaptopurine and Folic Acid Based on a Carbon Paste Electrode Modified with Zno-Cuo Nanoplates and 2-chlorobenzoyl ferrocene. (1st January 2017) - Beitollahi, Hadi; Ivari, Susan Ghofrani; Torkzadeh-Mahani, Masoud
Abstract : 2-chlorobenzoyl ferrocene, was synthesized and used to construct a modified ZnO-CuO nanoplates modified carbon paste electrode. The electrooxidation of 6-mercaptopurine at the surface of the modified electrode was studied. Under the optimized conditions, the square wave voltammetric (SWV) peak current of 6-mercaptopurine increased linearly with 6-mercaptopurine concentration in the range of 0.075 to 10.0 μM and 10.0 to 500.0 μM and a detection limit of 0.045 μM was obtained for 6-mercaptopurine. The diffusion coefficient and kinetic parameters such as electron transfer coefficient for 6-mercaptopurine oxidation were also determined. In addition, this modified electrode was used for simultaneous determination of 6-mercaptopurine and folic acid. Finally, the modified electrode was used for determination of mercaptopurine and folic acid in pharmaceutical and biological samples.